Find the equation of the hyperbola whose asymptotes are 2x – y = 3 and 3x + y – 7 = 0 and which passes through the point (1, 1). Find the equation of the corresponding conjugate hyperbola.
(2x – y – 3) (3x + y – 7) = 6
(2x – y – 3) (3x + y – 7) = -6
(2x – y – 3) (3x + y – 7) = 0
none of these
As we learned
Conjugate Hyperbola -
- wherein
The equation of the hyperbola differs from the equation of the asymptotes by a constant
The equation of the hyperbola with asymptotes 3x + y – 7 = 0 and 2x – y = 3 is
(3x + y – 7) (2x – y – 3) + k = 0
It passes through (1, 1)
k = –6
Hence the equation of the hyperbola is (2x – y – 3) (3x + y – 7) = 6
i.e., (3x + y – 7) (2x – y – 3) + 6 = 0
Study 40% syllabus and score up to 100% marks in JEE
Ask your Query
Register to post Answer